Spotlight on Music Collections: Interview with Marion Newman, (Ne’ega,) Mezzo-Soprano - Newman, Marion; Folk-Farber, Kyra (CAML Review / Revue de l’ACBM, 2024)
While previous Spotlight columns have focused on music collections and archives in Canada through the voices of those who work with them, this interview takes a slightly different angle by focusing on the career of Mezzo Soprano Marion Newman (Nege’ga), an internationally recognized opera singer who will be joining the University of Victoria School of Music as Assistant Professor on July 1, 2024. Newman is known across Canada and worldwide for her performances of the works of living Indigenous composers. In this interview, Marion discusses navigating - and stretching the limits of - the modern world of opera while proudly bearing her identity as Kwagiulth and Sto:lo. She also reflects on the complexities of balancing Indigenous traditions with modern Western music practices, her experiences working with written, recorded, and published Indigenous-composed music when, traditionally, and the role that library collections may play in her work as a faculty member at the University of Victoria. The interviewer, Kyra Folk-Farber, is honoured to be good friends with Marion as well as former singing colleagues while they both lived in Toronto, and collaborating with Marion on this interview was, unsurprisingly, a total delight.